2013
DOI: 10.1080/01446193.2013.802364
|View full text |Cite
|
Sign up to set email alerts
|

Striving to achieve it all: men and work-family-life balance in Sweden and the UK

Abstract: Although there is a vast literature on issues of work-life balance, most of the research is grounded on the traditional view of work-life balance as a female-oriented entitlement. So far little attention has been paid to how men balance their work-life situations, especially the 'new men' who are keen to share the family care. We contribute to filling this gap by critically examining how male academics in construction-related departments at universities in Sweden and the UK construct their relationships with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This finding can be explained by the fact that today work–life issues are equally important for both genders in Turkey. According to Raiden and Raisanen (2013), women and men equally experience work–home interference because of more common contribution to the financial well-being and the care at home. Consequently, lack of work–life balance is a problem for men as well as for women (Emslie & Hunt, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding can be explained by the fact that today work–life issues are equally important for both genders in Turkey. According to Raiden and Raisanen (2013), women and men equally experience work–home interference because of more common contribution to the financial well-being and the care at home. Consequently, lack of work–life balance is a problem for men as well as for women (Emslie & Hunt, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Current societal and regulatory initiatives are aimed at encouraging men to actively engage in sharing the caring routines and the housework. Thus, new labels for men such as “new men”, “involved fathers”, and “working fathers” have emerged (Raiden & Raisanen, 2013). Consequently, it is important today to examine the work–life balance of both genders (Darcy et al., 2012; Emslie & Hunt, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that the flexible nature of the academic job was advantageous to family life and to parenting (e.g., Nikunen, 2012; Toffoletti & Starr, 2016). This flexibility allowed academics to spend time with their children (e.g., Eddy & Gaston-Gayles, 2008; Sallee & Pascale, 2012), to take their children to school and support their activities (e.g., Perrakis & Martinez, 2012; Raiden & Räisänen, 2013), and to attend to their sick children (e.g., Damiano-Teixeira, 2006; Rafnsdóttir & Heijstra, 2013; Sallee & Pascale, 2012; Weigt & Solomon, 2008).…”
Section: Synthesis Of Qualitative Findingsmentioning
confidence: 99%
“…Among the manifestations of the academics’ WFC were unusually long and late-night work hours—including weekends and holidays (e.g., Hall, Anderson, & Willingham, 2004; Raiden & Räisänen, 2013; Solomon, 2011; Takahashi et al, 2014), a lack of sleep (e.g., Damiano-Teixeira, 2006), the inability to disengage from work when they wished to do so (e.g., Santos, 2014), feeling guilty about failing to fulfill both personal and professional responsibilities (e.g., Sallee, Ward, & Wolf-Wendel, 2016); and mental absence when at home (e.g., Reddick et al, 2012; Takahashi et al, 2014). Such conflict could be partially attributed to the demanding nature of the academic job that will be discussed later in the findings.…”
Section: Synthesis Of Qualitative Findingsmentioning
confidence: 99%
“…"Likewise more research is needed to examine why the structure of the profession is so much more gender-balanced in Eastern Europe and whether any areas of 'good practice' can be adopted." Striving to achieve it all: men and work-family-life balance in Sweden and the UK 24 CME 2013 "So far little attention has been paid to how men balance their work-life situations, especially the 'new men' who are keen to share the family care." they enter male-dominated work, little research has discussed how sexual minorities-and particular lesbians-fare in such environments."…”
Section: Discussionmentioning
confidence: 99%